Board Diversity, Firm Risk-taking and Firm Performance: Empirical Evidence from India - Bhateja, Fiza (Gyan Management Journal, 2023)
The study examines the impact of board diversity on the firm risk-taking and firm performance of Indian firms. A subset of Nifty 200 Index companies has been analysed over the period of five years using Panel Regression (fixed-effects) and Dynamic Panel Regression. After controlling for several firms and governance variables, the results showed that board education diversity played significant positive role in influencing firm risk-taking ability whereas board experience diversity found to have no link. With respect to impact of board diversity on firm performance, board educational and board experience diversity had a significant negative influence on stock-based measure of firm performance whereas no relationship in case of accounting-based measure. This research is a novel attempt to study the impact of education and experience attributes of board and recognizes various board-level characteristics on the firm-risk and firm performance, particularly in the wake of the implementation of the Companies Act 2013 in India.
Keywords: Board Diversity; firm risk; firm performance; panel data regression; Dynamic Panel Regression